Nilai Īṡār dalam Perspektif Tafsir Tematik: Studi atas Ayat-Ayat Al-Qur’an tentang Solidaritas Sosial - Farid Hidayatallah; Mahmudin Bunyamin; Ahmad Muttaqin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The central idea in Islam is Īṡār, which expresses the mindset of prioritizing the needs of others above one’s own. The purpose of this study is to thoroughly understand the meaning of Īṡār in the Qur’an, investigate the historical background of its use, and relate it to the relevance of contemporary society. The method used is thematic interpretation (maudhu’i) with a qualitative approach, sourced from books, scientific journals, and turās books left by scholars, such as Tafsir Ibn Kathir, Tafsir Al-Azhar, and Tafsir Al-Misbah. Specifically, verses related to the meaning of Īṡār, such as QS. Al-Hasyr verse 9. Īṡār combines components of preference, priority, and superiority offered to others, reflecting the values ​​of sacrifice, empathy, and social solidarity. According to the research findings, Īṡār implies prioritizing the needs of others above oneself, rejecting evil, and offering benefits. There are two types of Qur’anic verses related to Īṡār: those that explicitly use the word asāra or its derivatives, and those that subtly convey the values ​​or principles of Īṡār. The implication of this research is to make a positive contribution to the development of a more socially just, compassionate, and equitable society by instilling the values ​​of solidarity, social concern, and sacrifice for the common good.